Case reports of subcutaneous pdC1INH in pregnancy and lactation: expanding treatment options for hereditary angioedema in Portugal - Pinhal, Ana Luísa; Santos, Natacha; Dias de Castro, Eunice (Frontiers in Allergy, 2025)
Hereditary angioedema (HAE) is a rare genetic disorder characterized by recurrent episodes of subcutaneous and/or submucosal angioedema. Pregnancy and breastfeeding may be associated with an increased frequency of attacks. Plasma-derived C1 inhibitor (pdC1INH) is the recommended first-line treatment for long-term prophylaxis (LTP) in these special populations. The pdC1INH currently available in Portugal is one intravenous (IV) formulation not approved for LTP, as are the other IV and subcutaneous (SC) formulations. This report documents the first cases of SC pdC1INH use during pregnancy and breastfeeding in Portugal. It describes two cases of 37-year-old women with HAE type 1 treated with SC pdC1INH as LTP during pregnancy and lactation. Both patients had been previously treated with tranexamic acid. In the first case, the patient was started on IV pdC1INH at 8 weeks' gestation due to clinical deterioration. Due to difficult IV access and inability to space out administrations, SC pdC1INH at a dose of 4,000 U (∼43.5 U/kg) every 72 h was started at 21 weeks' gestation. Administration intervals were progressively increased to 96 and later 120 h. LTP was continued throughout lactation. In the second case, LTP was not administered during pregnancy. However, after delivery, the patient experienced a worsening of angioedema episodes during breastfeeding, which persisted despite tranexamic acid treatment. SC pdC1INH was started six months postpartum at a dose of 2,000 U (∼45 U/kg) twice weekly. The administration interval was later increased to 120 h. Both patients remained free of angioedema episodes and reported no systemic adverse events. The safety of SC pdC1INH was consistent with reports in the literature. Overall, these positive results support the future use of SC pdC1INH in a broader population of pregnant and lactating women in clinical practice.